Chest Pain Beyond the Heart: The Role of Cocaine in Pneumomediastinum - Abdul Muhsen Abdeen; Olivia Lim; Samuel Crow; Victoria Watson (Annals of Internal Medicine: Clinical Cases)
Cocaine use can cause cardiovascular issues, notably acute coronary syndrome, but this case highlights a rare complication: pneumomediastinum. A 27-year-old woman, a first-time cocaine user, presented with chest pain and fluctuating consciousness. Her history included obesity, gastric sleeve surgery, and substance use. Findings of a physical examination revealed chest crepitus. Findings from an electrocardiogram were normal, and laboratory test results showed an elevated leukocyte count and D-dimer. Findings of a urine screen were positive for cannabinoids and cocaine. Imaging confirmed pneumomediastinum. After treatment of presumed mediastinitis, the patient was discharged free of symptoms and supplied with drug counseling resources. This case underscores the importance of considering diverse diagnoses in cocaine-related presentations of chest pain.